Hannah Renstrom: capstone - Renstrom, Hannah, artist (Colorado State University. Libraries, 2022)
The artist's statement: From a young age I fought art. Disregarding the passion and fulfillment I felt when I was creating while my academic environment pushed me towards a technical path. By a stroke of luck, or perhaps fate, I ended up in a drawing class at CSU. Here, I gave in to a creative path and began to pursue a career in graphic design. Although it felt like I had found art late when others knew who they were as artists, I had developed a devotion to art and collaborating with other artists that helped me through the self doubts. The universality of graphic design is what drove my love for the medium. Visual communication is a powerful voice and I was drawn to its ability to be simple or complicated, manipulate or inspire. A language that can be understood across the world but morphs to the culture and people around it. Design has always felt like a living being to me because I understood the people behind it and why they chose the elements they did. I want to be a part of that language of artists and designers who understand how to arrange colors and symbols in a way that persuades people in millions of different ways. I want to be a part of a dynamic and ever changing life-form.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design